Personal and organizational factors supporting Green HRM performance in the tourism industry - Komesty Sinaga, Endang; Suryadi, Edi; Lastaripar Goeltom, Andar Danova; Ucu Rakhman, Cecep; Susanto, Eko (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This study examines the relationship between employees’ green environmental behavior and environmentally friendly organizational performance. Using the SEM-PLS analysis method, this study involved 307 respondents of tourism actors by testing survey data in the form of structural models involving personal and organizational factors related to employees’ green environmental behavior. The findings show a positive and significant influence of employees’ green environmental behavior on the performance of environmentally friendly organizations. In addition, factors such as environmental literacy, environmental empowerment, and environmental leadership also have a significant influence on employees’ green environmental behavior. However, it was found that factors such as employee religiosity, green environment self-efficacy, and green environment training did not significantly influence them. The study provides new insights into factors influencing employees’ green environmental behavior and provides a solid foundation for developing workplace strategies and policies that support green environmental behavior.